Preterm delivery risk in women initiating antiretroviral therapy to prevent HIV mother‐to‐child transmission. Issue 4 (11th September 2013) - Short, C‐ES; Douglas, M; Smith, JH; Taylor, GP
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to describe the relationship between preterm delivery (PTD; < 37 weeks of gestation) and antiretroviral therapy in a single‐centre cohort of pregnant women with HIV infection. Methods A retrospective analysis of data for 331 women who received care in a dedicated HIV antenatal clinic between 1996 and 2010 was carried out. Data on first CD4 cell count and viral load (HIV‐1 RNA copies/mL) recorded in pregnancy, class and timing of antiretroviral therapy, gestational age at delivery, and risk factors for and causes of PTD were available from a clinical database. Results Overall, 13.0% of deliveries were preterm, of which 53% were severe preterm (< 34 weeks of gestation). The lowest rate of PTD was observed in women treated with zidovudine monotherapy (6.2%). Higher rates of PTD were observed in women starting combination antiretroviral therapy (cART) in pregnancy compared with women conceiving while on cART [odds ratio (OR) 2.52; 95% confidence interval (CI) 1.22–5.20; P = 0.011]. Of the women who were eligible for zidovudine monotherapy on the basis of CD4 counts and HIV viral load but who were treated with short‐term cART to prevent HIV mother‐to‐child transmission, 28.6% delivered preterm. Women on short‐term cART remained at the highest risk of PTD compared with zidovudine monotherapy in multivariate analysis (OR 5.00; 95% CI 1.49–16.79; P = 0.015). Conclusions The causes of PTD are multiple and poorly understood. The timing of initiation and type of antiretroviral therapy administered during pregnancy appear to contribute to PTD risk. Understanding this association should improve the safety of antiretroviral therapy in pregnancy without increasing the risk of transmission.